I am also here: Invisible Insurrections in temporary autonomous zones – a haunting - James, Qondiswa (Michaelis School of Fine Art, 2022)
The research investigates experiments with the socio-political functions of public art interventions and suggests that these actions are temporary ruptures which create ‘invisible insurrections' in a context of hyper-surveillance. The paper draws from Hakim Bey's poetic anarchy, “Temporary Autonomous Zones”, and uses his theories to think through the potentially explosive overlaps between public space, live performance, and insurrection. By first locating a history of Worker's Culture in the South African context, the research locates itself within a particular context of class struggle. Reading Augusto Boal, and his Invisible Theatre, the research calls in Theatre of the Oppressed methodologies in an attempt to find a more suitable language, both abstract and concrete, to articulate the need for building solidarity. The study is also interested in the demarcations between theatre, performance art, and live art, and how to sit comfortably between these practice as research methods. To this end, through Mark Fleishman, the research proposes “dwelling” as a mode of performance for the public live art space especially in relation to revealing what is not visible in marginalised terrains. Here, the paper thinks through the possibility of reappropriating invisibility in the system as a cloak for haunting. Themes discussed in the research include insurrection as opposed to revolution; the scope of cultural work in general and the possibility of an emergent worker's culture in the present; the possibility of liberated zones inside the matrix as it is currently mapped; memory-being-made in relation to the archive; in/visibility in connection to ghostlikeness and haunting; collective precarity in system; and the importance of passing moments of ‘seeing each other' to building solidarity in our search for more human ways of being together.